Understanding the Impact of Workplace Flexibility on Motivation and Job Satisfaction: An empirical study on employees based in financial capital of India - Jiwarajka, Ritika Surendra (2022)
Workplace flexibility has become an upcoming requirement for most employees. It is viewed as the need of the hour, given the changed dynamics of the corporate world. Employees have increasingly put great importance to flexible working arrangements being introduced at their workplace. It may either positively or negatively impact an employee’s motivation and job satisfaction. Workplace flexible arrangements, as many authors argue, effectively offer employees the autonomy to make valuable workplace decisions, freedom to schedule their work day according to their personal preferences and the choice of taking meaningful breaks. It also increases their productivity. Additionally, workplace flexibility enables employees to maintain an acceptable work-life balance and may also reduce their work-stress.